Disruptive Behavior in the Clinical Setting: Implications for Patient Safety. Issue 3 (May 2017) - Simpson, Kathleen Rice
Abstract : Disruptive clinician behavior continues to be a problem in the clinical setting and increases risk of preventable harm to mothers and babies. A new committee opinion from the American College of Obstetrician and Gynecologists offers updated information about this type of behavior in our practice specialty and how to address it.